Sterile necrotizing and non-necrotizing granulomas in a heart transplant patient with history of PTLD: A unique finding. (2019) - Piening, Nicholas; Saurabh, Saxena; Munoz Abraham, Armando Salim; Osei, Hector; Fitzpatrick, Colleen; Greenspon, Jose
Highlights: This is the first ever reported case of sterile granulomas in a patient with PTLD. PTLD is a disease that could potentially be diagnosed with minimally invasive biopsy rather than diagnostic splenectomy. This report is to create awareness regarding potential presence of sterile granulomas and discuss use of biopsy before splenectomy. Abstract: Introduction: Posttransplant lymphoproliferative disease (PTLD) is a known complication in patients with solid organ transplant. It can present as localized or disseminated tumor. The cornerstone of management consists of reduced immunosuppression (RI). In select cases, localized disease can potentially be curative with surgical excision. Presentation of case: Here we present a case of a 19-year-old female with orthotopic heart transplant with two episodes of recurrent PTLD. After the second episode she was found to have asymptomatic splenic lesions which were refractory to RI and chemotherapy. She subsequently underwent splenectomy that showed sterile necrotizing and non-necrotizing granulomas with no evidence of PTLD. Discussion: Based on our literature search this is the first ever reported case of sterile granulomas in a patient with recurrent PTLD which could potentially be diagnosed with minimally invasive biopsy rather than diagnostic splenectomy. Conclusion: This report is an attempt to create awareness regarding potential for presence of sterile granulomas in patients with recurrent PTLD and discuss the use of percutaneous biopsy before splenectomy.